Profil Status Vitamin D, Aktivitas Fisik dan Kesehatan Paru pada Tukang Bangunan - Amelia Lorensia; Rivan Virlando Suryadinata; Ni Luh Mitha Rini Chandra (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: Construction workers tend to be exposed to air pollution which reduces lung function. Vitamin D is a factor that is closely related to a person's lifestyle. Including physical activity can improve lung function and vitamin D. Aim of study: This study aims to determine the profile of vitamin D, physical activity, and lung health in builders. Method: This research was conducted in September 2018-January 2019, which is located in East Surabaya. This study used a data collection technique with a questionnaire to measure vitamin D status and physical activity. Meanwhile, the measurement of lung function is by measuring the value of the FEV1 / FVC (forced expiratory volume in the first one second to the forced vital capacity) ratio using spirometry. The research sample was a pedicab driver without respiratory problems. The data analysis used is descriptive using profiles of vitamin D status, physical activity, and lung function conditions. Results and discussion: The majority of respondents experienced vitamin D deficiency as many as 120 people (75.95%). Most of the respondents also had heavy physical activity (48.73%). Meanwhile, regarding lung health, as many as 50% of people do not have lung function disorders, and some have mild (37.34%) and severe (12.66%) lung disorders. Conclusion: Construction workers are at risk for vitamin D deficiency and pulmonary function disorders, despite having a heavy level of physical activity.